Acid-catalyzed intramolecular ring-opening reactions of cyclopropanated oxabenzonorbornadienes with alcohol nucleophiles. Issue 45 (7th November 2019) - Wicks, Christopher; Koh, Samuel; Pounder, Austin; Carlson, Emily; Tam, William
Graphical abstract: Highlights: Intramolecular ring-opening of cyclopropanated oxabenzonorbornadienes were studied. This simple method allows the formation of medium-sized ring frameworks. Longer tether lengths gave exclusively Type 3 ring opened products in good yields. Good functional groups tolerance with good regioselectivities. Abstract: An investigation of intramolecular ring-opening reactions of various cyclopropanated oxabenzonorbornadienes (CPOBDs) with alcohol nucleophiles is reported, which forms two regioisomeric products in good yields. The effect of various tether lengths was explored, wherein increasing the alcohol tether length to 4 or 5 carbons exclusively generated Type 3 products in good yield, while C-1-hydroxymethyl substituted CPOBD formed a 1, 3, 5-cycloheptatriene derivative in excellent yield. Electron donating arene and electron withdrawing C-5-bridgehead substituents formed Type 3 major products, whereas electron withdrawing arenes and electron donating C-5 substituents preferentially afforded Type 2 compounds. A mechanism is also proposed for the formation of both regioisomeric products.